Interval Valued Intuitionistic Fuzzy Weak Bi-Ideals of Gamma Near-Rings - Arulmozhi, K.; Chinnadurai, V.; Swaminathan, A. (International Journal of Engineering and Technology, 2018)
In this paper, we introduce the concept of interval valued intuitionistic fuzzy weak bi-ideals of Î“-near-rings is a generalized concept of interval valued fuzzy weak bi-ideals of Î“- near-rings. We also characterize some results and illustrate our examples.Â